Application of Optical Coherence Tomography and Contrast Sensitivity Test for Observing Fundus Changes of Patients With Pregnancy-Induced Hypertension Syndrome. Issue 44 (November 2015) - Wang, Zhixue; Zou, Yuanyuan; Li, Wenying; Wang, Xueyan; Zhang, Min; Wang, Wenying
Abstract : Abstract: This study was aimed to investigate the fundus changes of patients with pregnancy-induced hypertension syndrome (PIHS) using optical coherence tomography (OCT) technology and contrast sensitivity (CS) tests. Ninety-eight patients with PIHS underwent routine eye examinations including vision correction, fundus examination, OCT, and CS tests. The CS test was performed at low, medium, and high frequency, respectively. Moreover, the difference in CS tests between 2 groups was analyzed by independent-samples T test. The Kruskal–Wallis rank sum test and linear regression model were used to detect the correlation of OCT with CS, respectively. Meanwhile Satterthwaite approximate T test was adopted for pairwise comparisons after nonparametric analysis of variance. The OCT test revealed that 56.76% of the examined eyes showed shallow retinal detachment in the macula lutea and around the optic disk. The differences in CS at each spatial frequency between the case and control group were statistically significant ( P  < 0.01). Besides, OCT manifestations were associated with CS at each spacial frequency including 1.5, 3, 6, 12, and 18 frequency ( P  < 0.01). And patients with abnormal manifestations of OCT showed lower CS at each spacial frequency than those without abnormal OCT manifestations. What's more the OCT manifestation 1 showed the greatest impact on CS at each spacial frequency. The results showed that abnormal OCT manifestations were correlated with CS in PIHS. OCT and CS tests might be valuable methods in observing fundus changes for PIHS patients.